International workshop on biotechnology in agriculture : evolving a research agenda for the ICGEB, September, 17-22, 1985 - Natesh, S.; Chopra, V. L.; Ramachandran, S., 1934- (A.A. Balkema, 1988)
On plant molecular biology and biotechnology.